10 junge künstler aus Deutschland. - Museum Folkwang, Essen (Essen : Museum Folkwang, 1982)
Adamski, Hans Peter ; Bömmels, Peter : Dahn, Walter ; Dokoupil, Georg ; Fetting, Rainer ; Kever, Gerard ; Kunc, Milan ; Middendorf, Helmut ; Naschberger, Gerhard ; Salomé
10 junge künstler aus Deutschland, Museum Folkwang, Essen, 5. Februar 1982 - 21. März 1982
boek